ANALISIS HUBUNGAN PERILAKU KERJA INOVATIF DENGAN MODAL PSIKOLOGI - Angelina Alicia Sumigar; Steven Tubagus (Ra'ah: Journal of Sociology of Religion, 2023)
This study aims to examine and analyze the relationship between Innovative Work Behavior and Psychological Capital in employees of the Department of Agriculture and Fisheries of Tomohon City with the address of Kelurahan Matani Satu, Tomohon Tengah District. In this study, the correlational quantitative method was used, with 88 employees of the Agriculture and Fisheries Office of Tomohon City out of a total population of 131 people. Data collection was taken using a questionnaire. The analysis used in testing the research hypothesis is Pearson Product Moment correlation analysis. This analysis was carried out with the help of the SPSS for Windows version 25.0 program. The results of this study are that there is a positive and significant relationship between innovative work behavior and psychological capital of 0.625. These results indicate that the hypothesis Ha is accepted and the hypothesis H0 is rejected. This means that there is a positive relationship or correlation between the variable (X) innovative work behavior and the variable (Y) psychological capital where the more innovative work behavior increases, the more psychological capital increases with the determinant contribution of innovative work behavior and psychological capital of 39%. Based on these results it was concluded that there was a positive and significant relationship between innovative work behavior and psychological capital in employees of the Department of Agriculture and Fisheries in Tomohon City. So it shows that employees in the Agriculture and Fisheries Service of Tomohon City have innovative work behavior based on abilities in the form of idea exploration, idea generation, idea championing and implementation so that psychological capital (psychological capital) in the form of self-confidence, hope, optimism and work resilience becomes more good at showing performance.